Implementación de un centro de control de motores para procesos de fabricación. - Jiménez Tonato, Marco Antonio (2023)
This research project has focused on developing an advanced control system for optimizing the toilet paper manufacturing process, with special approach on the electrical energy efficient use and the times and productivity improvement, to achieve this, it has been implemented a control center, what uses four programmable logic controllers (PLC), one of which acts as a master and the other three as slaves. They have been made simulations in the Factory IO software to estimate the material transport times in the different processes involved in the manufacturing, what has allowed improving times and increasing efficiency of productivity by 24.05%. This improvement has had a significant positive impact on production, further, it has been implemented energy efficiency measures to warranty an equipment adequate useful life and to reduce excessive current consumption in the used motors in conveyor belts, for example, to reduce high costs, acquiring several equipment, which can reduce the stress, when starting the conveyor sash, it has been done use a single frequency inverter for reducing the motors starting currents in each of belts, by ensuring a longer useful life long. Likewise, it has been achieved a starting sequence adequate control each one of machines, controlled by the master PLC, which allows getting an entire manufacturing process more comprehensive vision, with this centralized approach in the control all motors involved each machine, it has been significantly the production process efficiency and effectiveness as a whole.